Upaya Perbaikan Citra Negara: Filipina Sebagai Tuan Rumah Penyelenggara SEA Games Tahun 2019 - Safitri, Ni Luh Elya; Priadarsini, Ni Wayan Rainy; Resen, Putu Titah Kawitri (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 2 No 1 (2022): Jurnal DIKSHI, 2022)
This research aims to explain the interests of the Philippines hosting the 30 th SEA Games. The country's image was bad because Philippines considered a home for terrorists then unsafe to visit. This researcher used a descriptive qualitative method. This research used the sport as an instrument of soft power to achieve the interests of the state as a concept. This concept explains how hosting a mega sport can seek as an opportunity by the state to achieve its national interests. This research then perceives the answer that hosting mega sport event can improve the country's image, and also has an impact on economic interests in the Philippines.